Responsibility Accounting: A Control Tool for Management - Khatun, Mosammat Fahima (Asian Accounting and Auditing Advancement, 2011)
Large organizations are segmented for the sake of effective managerial control. These segments are responsibility centers. The individual in charge of a segment has been assigned authority and responsibility to control his or her responsibility center. But the extent of controllability depends on various technical and behavioral aspects. The objective of goal congruence and success of the organization as a whole depends on the proper coordination among various responsibility centers and the consideration of various behavioral aspects related to the problem. Lean enterprise concepts only can be applicable ensuring proper communication and coordination between responsibility centers. Responsibility accounting is practiced somewhat satisfactorily at profitable enterprises in Bangladesh. JEL Classification Code: M14, M41, M49